Analisis Penerapan Pendekatan Etnosains dalam Pembelajaran Kimia Untuk Meningkatkan Literasi Sains pada Siswa - Alia, Risa (LPPM Universitas Negeri Jakarta, 2024)
According to PISA 2018, scientific literacy in Indonesia is still lower than in other countries. Scientific literacy skills are needed to understand scientific issues, the risks and benefits of science, as well as to understand the nature of students' science through Ethnoscience-based chemistry learning. From the results of a review of several articles, the aim is to analyze students' chemical literacy skills through an ethnoscience approach. Learning chemistry is closely related to everyday life and matters related to local wisdom. The method used is the libbiometric method using Mendeley, Google Scholar and VOSviewer. The results of the analysis show that the ethnoscience approach can significantly improve students' chemical literacy skills in chemistry learning. This approach is categorized as high with an N-gain value of 0.67<0.58<1.00 in the ability to increase chemical literacy. The application of ethnoscience in chemistry learning can provide significant benefits in increasing students' chemical literacy.